Open source software as a service : provision of open sourcesoftware components to web application developers - Calpy, Daniel (2010)
Over different periods, open source software and Cloud computing have both been described as the next level of evolution in the software industry. Proponents of both paradigms have investigated different approaches to develop, use and create viable business models around computer software. The advantages offered by open source software and cloud computing are often contrasted against the more traditional approaches to software development and product consumption. However, very few studies have attempted to investigate the possibility of merging the attributes of open source software and cloud computing in order to achieve operational and business efficiency. Previous researches on open source software have identified some problems related to its adoption by potential users. In most cases, open source software has been regarded as a concept which should be left for IT savvy users. Although it boasts of considerable success at the back end and system level, open source software applications have not been very friendly to the non technical end user while problems related to intellectual property rights issues (copyright and patents), software support and maintenance have been identified as major inhibiting factors. Nonetheless, the benefits of open source software cannot be overlooked. In a bid to harness the benefits of open source software and mitigate some of its associated disadvantages, this research seeks for a method of circumventing the challenges related to IPR and support while providing and using open source software to provide an integrated service to a target market of high end users (application developers) . The purpose of this thesis is to find out how open source software can be offered as part of a service mix for web application developers, identify the characteristics of the primary adopters of the service and the legal, technical and economic constraints which limit its adoption and implementation. This study proposes a generic business model framework for the provision of web application development platform which leverages the strengths of open source software while mitigating some of its drawbacks and targeting a more sophisticated user segment. Increased competition, a need to produce a user centric application at competitive costs, a strong desire to reduce development cycles, tap unto a wide pool of human resource and reach a global market makes it necessary to investigate the idea of leveraging platform as a service and open source software to create new business models.